I would recognize him by his voice…The case of Emilio Berkhoff (ALPHA. Journal of Arts, Literature and Philosophy, 2020)
During the commission of a crime, witnesses or victims, exposed to the speech of the aggressor can be called, later, to recognize the voice of the person suspected of being the perpetrator of the crime, in order to establish whether they would recognize it as the voice of the offender. An example of this situation, where the testimony of hearing witnesses was involved, was during the case of Emilio Berkhoff (Chile, 2015), the young university student who was found guilty of the crimes of illegal bearing of arms and ammunition and sentenced to five years and one day in jail. The case was not exempt from some controversy due to the public statements of the accused about alleged violations of due process. In this paper we review the procedure used to collect the auditory evidence in light of the most widely shared criteria on the subject.
Keywords: Voices identification in forensic contexts; speaker recognition by naïve earwitness